A comparison of the HIPERLAN - Doufexi, A. (IEEE Communications magazine)
At present, WLANs supporting broadband multimedia communication are being developed and standardized around the world. Standards include HIPERLAN/2, defined by ETSI BRAN, 802.11a, defined by the IEEE, and HiSWANa defined by MMAC. These systems provide channel adaptive data rates up to 54 Mb/s (in a 20 MHz channel spacing) in the 5 GHz radio band. An overview of the HIPERLAN/2 and 802.11a standards is presented together with software simulated physical layer performance results for each of the defined transmission modes. Furthermore, the differences between these two standards are highlighted (packet size, upper protocol layers etc.), and the effects of these differences on throughput are analyzed and discussed